EGCG ameliorates high‐fat– and high‐fructose‐induced cognitive defects by regulating the IRS/AKT and ERK/CREB/BDNF signaling pathways in the CNS. Issue 11 (31st July 2017) - Mi, Yashi; Qi, Guoyuan; Fan, Rong; Qiao, Qinglian; Sun, Yali; Gao, Yuqi; Liu, Xuebo
Abstract : Obesity, which is caused by an energy imbalance between calorie intake and consumption, has become a major international health burden. Obesity increases the risk of insulin resistance and age‐related cognitive decline, accompanied by peripheral inflammation. (—)‐Epigallocatechin‐3‐gallate (EGCG), the major polyphenol in green tea, possesses antioxidant, anti‐inflammatory, and cardioprotective activities; however, few reports have focused on its potential effect on cognitive disorders. In this study, our goal was to investigate the protective effects of EGCG treatment on insulin resistance and memory impairment induced by a high‐fat and high‐fructose diet (HFFD). We randomly assigned 3‐mo‐old C57BL/6J mice to 3 groups with different diets: control group, HFFD group, and HFFD plus EGCG group. Memory loss was assessed by using the Morris water maze test, during which EGCG was observed to prevent HFFD‐elicited memory impairment and neuronal loss. Consistent with these results, EGCG attenuated HFFD‐induced neuronal damage. Of note, EGCG significantly ameliorated insulin resistance and cognitive disorder by up‐regulating the insulin receptor substrate‐1 (IRS‐1)/AKT and ERK/cAMP response element binding protein (CREB)/brain‐derived neurotrophic factor (BDNF) signaling pathways. Long‐term HFFD‐triggered neuroinflammation was restored by EGCG supplementation by inhibiting the MAPK and NF‐κB pathways, as well as the expression of inflammatory mediators, such as TNF‐α. EGCG also reversed high glucose and glucosamine‐induced insulin resistance in SH‐SY5Y neuronal cells by improving the oxidized cellular status and mitochondrial function. To our knowledge, this study is the first to provide compelling evidence that the nutritional compound EGCG has the potential to ameliorate HFFD‐triggered learning and memory loss.—Mi, Y., Qi, G., Fan, R., Qiao, Q., Sun, Y., Gao, Y., Liu, X. EGCG ameliorates high‐fat– and high‐fructose‐induced cognitive defects by regulating the IRS/AKT and ERK/CREB/BDNF signaling pathways in the CNS. FASEB J. 31, 4998–5011 (2017). www.fasebj.org